Aspergillus terreus Fungal Spondylodiscitis in a Healthy Patient Post-Lumbar Spine Surgery: A Rare Case Report - Mulukutla, Raghava D.; Yelamarthy, Phani Krishna Karthik; Krishna Narayan, Thiruvoipati Venkata; Kathare, Ambadas; Yeldandi, Vijay V. (Asian Journal of Neurosurgery, 2025)
We present a case of hospital-acquired Aspergillus terreus spondylodiscitis following lumbar spine surgery. The objective is to highlight the need for a high index of suspicion for rare fungal pathogens as causative organisms in postoperative spinal infections. A 39-year-old female underwent posterior decompression, stabilization, and interbody fusion at L4–5. Six weeks post-surgery she developed fever, back pain, and right leg pain. A diagnosis of postoperative spinal infection was made. On exploration and debridement of the wound, the fungal cultures grew positive for A. terreus. She was treated with voriconazole for 6 months. Following debridement and antifungal therapy, symptoms and inflammatory markers subsided over a period of time. There was no recurrence of infection till the last follow-up at three and half years. To the best of our knowledge, this is the only case report of an A. terreus spondylodiscitis following lumbar spine surgery. The possibility of fungal infection should be considered in elderly and immune-compromised patients. In our institution, all postoperative spinal infections, irrespective of age and comorbidities, are subjected to microbiological cultures including fungal cultures and sensitivities. Thorough debridement, involvement of infection control specialists, and use of long-term antifungal therapy help resolve these infections.
Keywords: Aspergillus terreus; fungal infection; spondylodiscitis; surgical site infection; osteomyelitis